Peningkatan Pengetahuan Mengenai Manfaat Pangan Probiotik dan Prebiotik Bagi Kesehatan - Rifatul Masrikhiyah; Henry Widya Prasetya; Ubaedillah Ubaedillah; Rifqi Ferry Balfas; Susi Yulianingsih (LPPM Universitas Muhadi Setiabudi, 2020)
Probiotics are foods or drinks that contain live bacteria that benefit or benefit health, whereas prebiotic is a foodstuff that is not digestible by digestive enzymes and can support the growth of good bacteria in the intestines. The magnitude of probiotic food benefits and prebiotics for health as reported by Healthline, prebiotic food and probiotics are effective for treating diarrhea, irritable bowel syndrome, allergic disorders, but the enrichment regarding probiotic and prebiotic food is very lacking. This activity aims to improve the knowledge of the probiotic food benefits and prebiotics for health. . PkM was held in the village Sidamulya Wanasari Kabupeten Brebes subdistrict in November 2019. The subject that follows the activity of 25 mothers-Ibu Posyandu Kader Sidamulya Village. This activity consists of 3 stages including: preparation stage, implementation stage and interview stage. Data obtained from pretests and posttest results and discussions. Results of this activity is an increase in the knowledge of mothers about the benefits of food probiotics and prebiotic for health, there is an increase from 4% to 68%.